PENGARUH GAYA KEPEMIMPINAN IOWA KEPALA SEKOLAH TERHADAP PENINGKATAN MUTU PENDIDIKAN DI MAN 2 GRESIK - Ananda Ditasari; Wahyu Puteri Pratama; Azizah Lailatus Syifa; Riqa Dwinur Aisyah; Erny Roesminingsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted with the aim of analyzing the leadership practices of the principal of MAN 2 Gresik in supporting students’ academic achievement and global competitiveness. The research was conducted through interviews with the principal of MAN 2 Gresik. The research design used was quantitative descriptive; the data obtained were derived from a questionnaire distributed to 34 respondents. Analysis was performed using correlation tests and simple linear regression using SPSS software. The research results passed the validity and reliability tests. Variable Y did not meet the assumption of normality (Shapiro-Wilk sig. = 0.000) and heteroscedasticity was detected (Glejser sig. = 0.007 < 0.05), so the non-parametric Spearman Rho was used. The analysis results showed a significant positive correlation (r_s = 0.473; sig. = 0.005 < 0.01), which is classified as a moderate relationship. The regression equation is Y = 31.465 + 0.536X with R² = 0.260, meaning that Iowa leadership explains 26% of the variance in educational quality. The implementation of Iowa leadership contributes synergistically to improving educational quality at MAN 2 Gresik.